Small engines, their fuels and the environment : the friendly conference - International Conference on Small Engines, their Fuels and the Environment (5th : 1995 : United Kingdom); University of Reading. Department of Engineering. The Energy Group; IT Power Ltd, UK; Institute of Energy (Great Britain); Sustainable Engine Systems (SES) Ltd (United Kingdom : University of Reading, 1995)
20